2014
DOI: 10.1051/ocl/2014033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sunflower oils obtained separately by pressing and subsequent solvent extraction from a new line of seeds rich in phytosterols and conventional seeds

Abstract: -In this study we evaluate the chemical composition of sunflower oils obtained separately by pressing and subsequent solvent extraction from a new seeds rich in phytosterols (IASP-18) and conventional seeds . Results have shown that the total content of oil was much lower in the IASP-18 (18.1%) than in the conventional (37.5%) seeds. The extraction yield obtained by pressing was as low as 3% in the IASP-18 seeds and 37.5% in HA-89, while in the solvent extraction it was of the same order (∼18 wt% on seeds extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Farmyard manure and a balanced chemical fertilizer seem to contribute to better aggregation, thereby increasing effective pore volume. Given the dependence of soil permeability on effective pore volume, one may suggest a direct impact in terms of improved pore volume upon applying FYM on the K sat of soil [34]. According to the results, the RT system with combined FYM + 50% of the recommended dose chemical NPK fertilizer application could increase K sat significantly, possibly because of decreased density.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Farmyard manure and a balanced chemical fertilizer seem to contribute to better aggregation, thereby increasing effective pore volume. Given the dependence of soil permeability on effective pore volume, one may suggest a direct impact in terms of improved pore volume upon applying FYM on the K sat of soil [34]. According to the results, the RT system with combined FYM + 50% of the recommended dose chemical NPK fertilizer application could increase K sat significantly, possibly because of decreased density.…”
Section: Discussionmentioning
confidence: 92%
“…Also, an increase in soil moisture was recorded for the second year. In this regard, some previous studies also suggested that inorganic fertilization can indirectly increase SOM by improving the root biomass compared to control plots [34,35].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rao et al (1998) concluded that the squalene reduces the risk of colon cancer and the serum cholesterol level. Few studies have focused in the variability of squalene in sunflower oil, Merah et al (2012) reported a variation from 10 to 202 mg/kg Data from Aguirre et al, 2007Aguirre et al, , 2014Gunstone, 2011; ND = Non Detected; SO = Sunflower Oil; HOSO: High Oleic Sunflower Oil, MOSO = Mid Oleic Sunflower Oil.…”
Section: Others Terpenoidsmentioning
confidence: 99%
“…3) being β-sitosterol the main sterol. Phytosterol content is mainly affected by environmental conditions during plant growth (Ayerdi Gotor et al, 2015) and genetics (Aguirre et al, 2014;Fernández-Cuesta et al, 2011) but there is no effect of the modification of the fatty acids profile (Ayerdi Gotor et al, 2014).…”
Section: Phytosterolsmentioning
confidence: 99%